Iqamatu wa Batsu Shalah al-Jama’ah Fi Mushallah Bere’ Songai, Bungur, Potoan Daya - Supriyadi, Moh.; Jalaluddin, Ach.`; Yakin, Nurul; Alimakki, Moh.; Fauzi, Moh. (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2023)
Prayer awakens people so that they are always aware that they are God's servants who must serve Allah SWT. Prayer has such an important place that it is used as a measure in Islam. This is in Islam, there are several types of prayer that are associated with certain times and moments, such as obligatory prayers, namely prayers which are divided into five times, Eid al-Fitr prayer, Eid al-Adha prayer, and so on, after the prayer there is still another prayer known as ba'diyah prayer, it shows the importance of prayer in Islamic teachings. Congregational prayers in Islam are very beneficial in increasing enthusiasm, equality and brotherhood, and can create bonds of love and mutual understanding among other Muslims. It aims to evoke a sense of togetherness. Congregational prayer is highly recommended for every Muslim to get priority reward. Every Muslim will feel the wisdom of congregational prayer in himself in living his daily life as a human being. People who pray in congregation will also receive double reward compared to praying alone. The congregational prayer activities are not only carried out at home, prayer rooms, Surau or mosques but are also taught in different environments. Congregational prayers will be performed frequently, especially by children who are studying